2018
DOI: 10.1097/md.0000000000011976
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic lactoferrin for preventing late-onset sepsis and necrotizing enterocolitis in preterm infants

Abstract: Current evidence indicates that lactoferrin could significantly reduce the incidence of NEC and LOS, and decrease the risk of hospital-acquired infection and infection-related mortality in premature infants without obvious adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 29 publications
1
25
0
1
Order By: Relevance
“…A Cochrane Review of six, small, randomized control trials (RCT) that provided lactoferrin supplementation to enteral feeds found decreased late-onset bacterial and fungal sepsis in preterm infants, although the evidence was identified as low in quality [16]. A systematic review and meta-analysis reviewed nine RCTs and showed that prophylactic lactoferrin significantly reduced the incidence of late-onset sepsis and NEC (Bell's stage II or greater) [17]. Most recently, a large randomized control trial of 2203 infants contrasted these prior findings, demonstrating that enteral supplementation with bovine lactoferrin did not reduce NEC or the incidence of infection or mortality [18].…”
Section: Lactoferrinmentioning
confidence: 99%
“…A Cochrane Review of six, small, randomized control trials (RCT) that provided lactoferrin supplementation to enteral feeds found decreased late-onset bacterial and fungal sepsis in preterm infants, although the evidence was identified as low in quality [16]. A systematic review and meta-analysis reviewed nine RCTs and showed that prophylactic lactoferrin significantly reduced the incidence of late-onset sepsis and NEC (Bell's stage II or greater) [17]. Most recently, a large randomized control trial of 2203 infants contrasted these prior findings, demonstrating that enteral supplementation with bovine lactoferrin did not reduce NEC or the incidence of infection or mortality [18].…”
Section: Lactoferrinmentioning
confidence: 99%
“…Laktoferrin ist ein in der Muttermilch enthaltenes Glykoprotein mit immunmodulatorischen Eigenschaften. He et al kamen in einem systematischenReviewderbisdahinveröffentlichtenrandomisierten Studien mit insgesamt 1834 Patienten zum Ergebnis, dass die oraleGabevonLaktoferrineinesignifikanteReduktionderKulturpositiven LOS, der NEC und der Mortalität durch Infektionen bewirkte [136]. Allerdings waren die in diesem Review eingeschlossenen Studien u. a. hinsichtlich der Inzidenz der Pilzsepsis sehr heterogen.IndernachdemReviewvonHeetal.veröffentlichten ELFIN Studie mit 2.203 Patienten hatte die Gabe von bovinem Lak-toferrinkeinenEinflussaufdasRisikoderLOS(RR0,95;95%CI0,86-1,04; p = 0,233) [137,138].…”
Section: Prävention Der Los Durch Laktoferrinunclassified
“…Lactoferrin is an important protein consumed by breast-fed new born infants, with the highest concentration in colostrum (range 6-7 g/L) and a relatively lower concentration in mature milk (range 1-5 g/L). 2 As a multifunctional protein protective against infection and inflammation, lactoferrin has been used as a supplement for human infant formula. 3 Lactoferrin is also present in bovine milk at a concentration of 0.2 to 1.5 g/L with over 70% amino acid homology compared to human lactoferrin.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Though several studies investigated multiple aspects of lactoferrin function, the underlying mechanism of its protective effect during NEC progression remains unclear, and its protective effects on the early stages of NEC is still controversial. 2,11 Therefore, we sought to elucidate the mechanisms driving lactoferrinmediated protection during NEC progression, especially focused on its regulation of inflammation and cell proliferation. Furthermore, we administered lactoferrin on healthy pup mice to verify its safety and test for adverse effects.…”
Section: Introductionmentioning
confidence: 99%